Differences in admitting hospital characteristics for black and white Medicare beneficiaries with AMI - Popescu, Ioana (2011)
BACKGROUND: Racial disparities in acute myocardial infarction (AMI) treatment may be due to differences in admitting hospitals. Little is known about factors associated with hospital selection for black and white AMI patients. METHODS AND RESULTS: We identified black and white Medicare beneficiaries with AMI in 63 hospital referral regions (HRRs) with at least 50 black admissions during 2005 (N=65,633). We calculated distance from patient home to HRR hospitals using zip code centroids. We assessed hospital quality using a composite score comprised of hospital risk-adjusted 30-day mortality and AMI performance measures. Hospitals with a score in the top 20% were categorized as high-quality and lowest 20% as low-quality. We used conditional multinomial logit models to examine differences in hospital selection for blacks and whites. On average, blacks lived closer to revascularization hospitals (mean 3.8 vs. 6.8 miles, p<.001) and to high-quality hospitals (mean 5.6 vs. 9.7 miles, p<.001). After accounting for distance, blacks were relatively less likely (p<.001) to be admitted to revascularization hospitals (RR 0.87, 95%CI 0.80-0.95), and to high-quality hospitals (RR 0.88, 95%CI 0.801-0.95), but more likely (p<.001) to be admitted to low-quality hospitals (RR 1.17, 95%CI 1.05-1.29). In analyses matched by home zip code, differences in admissions to revascularization (RR 0.92, 95%CI 0.80-1.05), high- (RR 0.94, 95%CI 0.81-1.07) and low-quality (RR 1.15, 95%CI 0.94-1.35) hospitals were not significant. CONCLUSIONS: Differences in admissions to revascularization and high-quality hospitals may contribute to disparites in AMI care. These differences may be due in part to residential zip code characteristics.